2013
DOI: 10.1016/j.vetpar.2013.07.032
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of heather extracts on Trichostrongylus colubriformis eggs, larvae and adults

Abstract: This study was carried out to evaluate the in vitro effects of different heather species on Trichostrongylus colubriformis eggs, larvae and adult worms, and obtain scientific evidence to attribute these effects to the action of their phenolic compounds and/or tannins. Total phenolic extracts of three heather species (Calluna vulgaris, Erica cinerea, and Erica umbellata) and an equal mixture of these three extracts were tested in vitro in the three development stages of T. colubriformis using an egg hatching as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Testing of all extracts for their AH activity showed the strongest activity for the acetone/H 2 O (70:30) extract (Figure , Table ), a result that coincided with earlier in vitro reports (Castañeda‐Ramírez, ). Extracts from MeOH/H 2 O (1:1), MeOH, and MeOH‐ES showed moderate activity with IC 50 values ranging from 115 to 900 μg/mL; these values are similar to those reported for extracts from other plants, when evaluated against H. contortus using the same bioassay (Castañeda‐Ramírez, ; Moreno‐Gonzalo et al ., ; Vargas‐Magaña, ). The lack of AH activity in extracts from medium (EtOH) to low polarity solvents (CH 2 Cl 2 ‐SE and EtOAc‐SE) further confirmed the finding that the bioactive metabolites of L. latisiliquum are of high polarity (Hernández‐Bolio et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Testing of all extracts for their AH activity showed the strongest activity for the acetone/H 2 O (70:30) extract (Figure , Table ), a result that coincided with earlier in vitro reports (Castañeda‐Ramírez, ). Extracts from MeOH/H 2 O (1:1), MeOH, and MeOH‐ES showed moderate activity with IC 50 values ranging from 115 to 900 μg/mL; these values are similar to those reported for extracts from other plants, when evaluated against H. contortus using the same bioassay (Castañeda‐Ramírez, ; Moreno‐Gonzalo et al ., ; Vargas‐Magaña, ). The lack of AH activity in extracts from medium (EtOH) to low polarity solvents (CH 2 Cl 2 ‐SE and EtOAc‐SE) further confirmed the finding that the bioactive metabolites of L. latisiliquum are of high polarity (Hernández‐Bolio et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In this review, antiparasitic effects of plants vary depending on the plant species, stage, the nematode species and the parasitic stage. Erica cinera was more active against eggs and L 3 of T. columbriformis than to inhibit the egg hatching and larvae exsheathment of abomasal parasites ( H. contortus and T. circumcinta ) (Moreno-Gonzalo et al ., 2013 a , 2013 b ). The Agave sisalana and Moringa oleifera has greater ovicidal effect while Acacia nilotica and A. raddiana are more active against L 3 of GIN (Botura et al ., 2013; Zabré et al ., 2017; De Medeiros et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, antiparasitic effects of plants vary depending on the plant species, stage, the nematode species and the parasitic stage. Erica cinera was more active against eggs and L 3 of T. columbriformis than to inhibit the egg hatching and larvae exsheathment of abomasal parasites (H. contortus and T. circumcinta) (Moreno-Gonzalo et al, 2013a, 2013b (Chan-Pérez et al, 2016). The use of standardized in vitro methods is essential for the assessment of the efficacy of plant products, particularly the determination of EC 50 and EC 90 (effective concentration 50% and 90%), which allows the comparison of activities of different plants (Borges and Borges, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extracts of Garlic (Allium sativum L.) were found to reduce coccidial load and enhance goat performance [65]. Similar studies that have shown the anthelmintic effect of plant extracts and essential oils are [66,67].…”
Section: Plant Extracts and Essential Oilsmentioning
confidence: 90%